Fluorescence Lifetime–Based Competitive Binding Assays for Measuring the Binding Potency of Protease Inhibitors In Vitro. (July 2014) - Boettcher, Andreas; Gradoux, Nathalie; Lorthiois, Edwige; Brandl, Trixi; Orain, David; Schiering, Nikolaus; Cumin, Frederic; Woelcke, Julian; Hassiepen, Ulrich
Fluorescence lifetime (FLT)–based assays have developed to become highly attractive tools in drug discovery. All recently published examples of FLT-based assays essentially describe their use for monitoring enzyme-mediated peptide modifications, such as proteolytic cleavage or phosphorylation/dephosphorylation. Here we report the development of competitive binding assays as novel, inhibitor-centric assays, principally employing the FLT of the acridone dye Puretime 14 (PT14) as the readout parameter. Exemplified with two case studies on human serine proteases, the details of the rationale for both the design and synthesis of probes (i.e., active site–directed low-molecular-weight inhibitors conjugated to PT14) are provided. Data obtained from testing inhibitors with the novel assay format match those obtained with alternative formats such as FLT-based protease activity and time-resolved fluorescence resonance energy transfer–based competitive binding assays.